MEASURING THE OPPORTUNITIES AND THREATS OF INDONESIAN FISHERY PRODUCT TRADE WITH JAPAN IN THE APEC FRAMEWORK: A CASE STUDY OF FISHERY PRODUCT EXPORTS - Fauziyah, Syahwatul Khalda (Samudra Publisher, 2025)
This article discusses the dynamics of processed fishery product trade between Indonesia and Japan within the framework of the Asia Pacific Economic Cooperation (APEC). The main focus of this study is to examine the opportunities and challenges faced by Indonesia in increasing its exports of processed fishery products, such as canned tuna, surimi, and fish fillets, to the Japanese market. Through an analysis of recent years’ export data and applicable trade policies, such as the Protocol Amendment to the Indonesia–Japan Economic Partnership Agreement (IJEPA), it was found that the elimination of import tariffs and the rising demand in Japan for high-quality seafood products provide significant opportunities for Indonesian products. Nevertheless, several challenges remain, including Japan’s strict food safety standards, competition with other major suppliers such as Thailand and Taiwan, and the need for regulatory harmonization between the two countries. This article also highlights APEC’s role in facilitating inclusive free trade through capacity building, policy dialogue, and alignment of product quality standards among member countries. In conclusion, by leveraging supportive trade policies and enhancing sustainable production capacity, Indonesia holds great potential to expand its market share of processed fishery products in Japan.